Taxonomic review of the subgenus Andrena (Poecilandrena) (Hymenoptera: Andrenidae) in Israel and the Levant - Pisanty, Gideon; Scheuchl, Erwin; Dorchin, Netta (Zootaxa, 2018)
Andrena (Poecilandrena) Hedicke is a subgenus of small solitary bees, with the greatest diversity in the Eastern Mediterranean Region—an important but understudied biodiversity hotspot for bees. We studied Andrena (Poecilandrena) collected mostly in Israel and the West Bank, and make several additions to the regional fauna. We provide the first comprehensive review of Andrena (Poecilandrena) species currently known from Israel, the West Bank, Jordan, Lebanon and Syria, including diagnostic keys to females and males, descriptions of new species and unknown sexes, and detailed information for each taxon regarding distribution, phenology and flower visitation. Our review includes fourteen species of Andrena (Poecilandrena) from the Levant, including five species new to science: A. freidbergi Pisanty & Scheuchl n. sp., A. galilaea Pisanty & Scheuchl n. sp., A. hierosolymitana Pisanty & Scheuchl n. sp., A. sedumella Scheuchl & Pisanty n. sp., and A. stenofovea Scheuchl & Pisanty n. sp. We also report four species as new to the region, and provide the first description of the male of A. rusticola Warncke. We exclude A. arabica Scheuchl & Gusenleitner from the subgenus, and synonymize it with A. helouanensis Friese. We anticipate that more collecting work in this region will yield additional undescribed taxa as well as new records, especially of taxa already known from Turkey. In the appendix to this work we provide information on 35 new records of other Andrena subgenera from Israel and the West Bank that have accumulated in recent years.